Concurrent deep UV diffractions enabled by the Bragg condition and crystal symmetry in silica inverse opals. (20th January 2021) - Rout, Dipak; Kumar, Govind; Vijaya, R
Abstract: Understanding the unexplored deep ultraviolet (UV) diffraction from photonic crystals will pave the way forward for developing diffractive optical elements in the deep UV wavelength range (190–250 nm). Herein we optically characterized the deep UV diffraction from our highly ordered 3D silica inverse opals fabricated by a co-assembly method and calculated their photonic band structures. Presence of a photonic stopband along their ΓL crystallographic direction is observed from the band structure. Presence of cracks and defects in these inverse opals impacts their deep UV photonic stopbands. Angle dependent diffraction measurements quantify the spacing of the (111) planes in the face-centered cubic inverse opal. Laser diffraction in the deep UV range yields a hexagonally symmetric six-spot pattern surrounding a central bright spot associated with Bragg diffraction in these inverse opals. Unlike earlier work, this feature has been observed with light at multiple wavelengths well within the stopband. Analysis of the deep UV diffraction pattern leads to the possibility of concurrent Bragg diffraction and (111) plane symmetry derived diffraction from our inverse opal PhC that are wavelength dependent.